Iterative multiuser detection for turbo-coded asynchronous DS-CDMA over fading channels - Hu, Chuanzhen. (2008)
This thesis deals with various iterative multiuser detectors for the turbo-coded asynchronous direct-sequence code-division multiple access systems over fully-interleaved Rayleigh flat fading as well as frequency-selective fading channels.